PENILAIAN POTENSI DAYA TARIK OBYEK WISATA DANAU MUPA KENCANA KECAMATAN PUTUSSIBAU UTARA KABUPATEN KAPUAS HULU - Kekek, Lidia; Fahrizal, .; Dirhamsyah, . (Universitas Tanjungpura, 2016)
Kapuas Hulu is one of the city located in the province of West Kalimantan. Regency of Kapuas Hulu have some objects natural tourism that very interesting to visit. One of objects natural tourism is Danau Mupa Kencana located in the village of Pala Pulau, District of North Putussibau. Object natural tourism of Danau Mupa Kencana is one of place which managed by the department of tourism, Kapuas Hulu. Danau Mupa Kencana is an area that has potential and attractive as one of natural tourism. But in Therefore, needed research to asses Danau Mupa Kencana tour and to determine the feasibility of a tourism destination. The purpose of this research are to know and assess potential attractiveness contained in natural tourism area of Danau Mupa Kencana. This research using descriptive analytical method, which explains all the potential objects of attractiveness object of natural tourism in 2003. The results showed that Danau Mupa Kencana got a total score 741,98. From the results showed that Danau Mupa Kencana got value B, which means Danau Mupa Kencana enough potential to be developed as a place/natural tourism